Conventional papillary thyroid carcinoma with intraglandular lymphatic dissemination shows more aggressive features. (22nd July 2022) - Lei, Yuanyuan; Feng, Sha; Yu, Qiuxiao; Shen, Guihua; Yuan, Lijuan; Huang, Wenting
Abstract: Objective: To investigate the invasive capability and other clinicopathological features of conventional papillary thyroid carcinoma (CVPTC) with intraglandular lymphatic dissemination. Methods: Seventy-three conventional papillary thyroid carcinoma patients receiving total thyroidectomy were analyzed in this study. The expression of BRAF-V600E, D2-40 and CD31 in all thyroid samples was detected by immunohistochemical staining. The results were evaluated by two pathologists and were statistically analyzed. The rate of positive BRAF-V600E expression and the clinical invasiveness of CVPTC with intraglandular dissemination, multifocal non-intraglandular dissemination-CVPTC and single focus-CVPTC were evaluated. The correlation between BRAF-V600E expression, lymphatic vessel density, microvessel density and the clinicopathological characteristics of conventional papillary thyroid carcinoma were assessed. Results: Twenty-five intraglandular dissemination-CVPTC, 17 multifocal non-intraglandular dissemination-CVPTC and 31 single focus-CVPTC cases were included in this study. The results showed that BRAF-V600E expression was independently correlated with intraglandular dissemination, age and pN staging ( P  < 0.05). The lymphatic vessel density in the intraglandular dissemination-CVPTC group was higher than that in the non-intraglandular dissemination-CVPTC group ( P  < 0.05). Compared with cases without intraglandular dissemination, intraglandular dissemination-CVPTC was associated with a younger age, higher lymph node metastasis rate, pN staging, the expression of BRAF-V600E and increased Capsule invasion and lymphovascular tumor thrombus ( P  < 0.05). During the follow-up of 30 months (median 15 months), two patients in the intraglandular dissemination-CVPTC group had cervical lymph node metastasis after the first operation. Conclusions: Intraglandular dissemination-CVPTC shows more aggressive features, and intraglandular lymphatic dissemination may be a potential biological indicator of poor prognosis. Abstract : Intraglandular dissemination of conventional papillary thyroid carcinoma was correlated with BRAF-V600E, lymphovascular tumor thrombus and lymph node metastasis.